A retrospective-prospective study of the effect of octreotide LAR in acromegalic patients - Pemovska, Gordana; Volkanovska, Anche; Jovanoska, Biljana; Shubeska Stratrova, Slavica (My University, 2013)
Surgery is considered first-line treatment for pituitary GH secreting macro-adenoma. Since surgical removal of the pituitary tumor is subtotal, medical treatment has become the mainstay of acromegaly. The aim of our study was to assess the effect of octreotide LAR (OCT-LAR) therapy in patients with acromegaly. Patients and methods: Ten acromegalic patients were treated with OCT-LAR 20 mg/28 days. The effect was evaluated after 12 months of treatment. Eight patients received OCT-LAR as adjunctive therapy after surgical debulking, and two as primary treatment. Tumor size was assessed with pituitary magnetic resonance imaging (MRI) before the treatment and after 12 months. Biochemical evaluation was performed at baseline, 6 and 12 months after beginning OCT-LAR. Normalization of IGF1 was considered as biochemical remission of active acromegaly. Results: Among the evaluated patients five were males and five females, mean age 40.2G 8.04 years (age range: 30–50 years). After 12 months of treatment biochemical remission (normalization of IGF1 levels) of acromegaly was achieved in nine patients. Values of IGF1 after 6 and 12 months showed a mean decrease of 55.69 and 71.53% respectively. Average tumor size before treatment and after 12 months was 17.7 and 10.42 mm respectively with an average decrease of 48.18% in size. Also, GH levels were evaluated and showed a mean decrease of 74.57% after 12 months. Along the treatment significant improvements in headache, arthralgia, sweating and soft tissue swelling was attained. Conclusions: Treatment with OCT-LAR can be considered as effective therapy in achieving biochemical remission and tumor shrinkage in active acromegaly. Given its efficacy and safety it is a treatment of option as primary therapy in patients who are at risk or refuse operative treatment.
Keywords: Acromegaly; octreotide LAR; GH; IGF